1/4x+3/8 factored by the GCF

Answers

Answer 1
Answer:

Given:

(1)/(4)x+(3)/(8)

To find:

The factor form of given expression by the GCF.

Solution:

First we need to find the GCF of (1)/(4) and (3)/(8).

So, make denominators same.

(1)/(4)=(1* 2)/(4* 2)=(2)/(8)

Now,

GCF\left((2)/(8),(3)/(8)\right)=(1)/(8)

GCF\left((1)/(4),(3)/(8)\right)=(1)/(8)

We have,

(1)/(4)x+(3)/(8)

It can be written as

=(2)/(8)x+(3)/(8)

Taking out the GCF (1)/(8), we get

=(1)/(8)(2x+3)

Therefore, the required factor form is (1)/(8)(2x+3).


Related Questions

Jill had $125 to spend at the mall. She spent 27% of that money on a pair of shoes. Jill spent $___ on the shoes. (Make sure to enter the answer as a decimal number only. Do not enter special characters such as the dollar symbol.) Answer for Blank 1:
According to the Fundamental Theorem of Algebra, how many roots exist for the polynomial function? f(x) = 8x7 – x5 + x3+6
Ignore the top part. but can someone help me with part b please?
An airplane travels a distance of 42x^5y^4 miles in 6xy^2 hours. find the average speed of the plane
Round off 4252 to one significant figure

Admission to the county fair is $5. And it costs and additional $0.50 for each ride ticket. What inequality represents this problem

Answers

Y = 0.50x + 5.00 the base number being what everyone pays should be your b value and the number it increase by should be your m in the equation y=mx+b hope that helps:)

Please help !!!!!!!!!!!!-

Answers

3.(4p−2)(p−4)
=(4p+−2)(p+−4)

=(4p)(p)+(4p)(−4)+(−2)(p)+(−2)(−4)

=4p2−16p−2p+8

=4p2−18p+8

Simplified form - 
4p2−18p+8

4.
(2x2+4x−3)(3x+1)

=(2x2+4x+−3)(3x+1)

=(2x2)(3x)+(2x2)(1)+(4x)(3x)+(4x)(1)+(−3)(3x)+(−3)(1)
=6x3+2x2+12x2+4x−9x−3

=6x3+14x2−5x3

Simplified form - 
6x3+14x2−5x3

What is 12-3x=-6x
Show the work please

Answers

Answer:

x=-3

Step-by-step explanation:

12-3x=-6x

12=-3x-6x

12= -9x

----------

-9. -9

12/9= -3

X=-4
How I did it :
12 - 3x = -6x
Add 3 x to both sides:
12 = -3x
Then divide both sides by -3:
-4 = x
And just switch it around

Lionel computed the average rate of change in the depth of a pool over a two-week interval to be zero. Which statement must be true?The pool must have been empty for the entire interval.

The pool must have been the same depth at the start of the interval as it was at the end of the interval.

The pool must have been deeper at the end of the interval than it was at the start of the interval.

The pool must have been more shallow at the end of the interval than it was at the start of the interval.

Answers

Answer: The pool must have been the same depth at the start of the interval as it was at the end of the interval.

Explanation:

The average rate of change is calculated as:

[final value - initial value] / time interval.

Then, the average rate of change does not take into account intermediates values, and you cannot draw any conclusion about such intermediate values.

In the given case you have:

average rate of change in depth = [final depth - initial depth] / 2 weeks.

0 = [final depth - initial depth] / 2 weeks.

⇒ 0 = final depth - initial depth

final depth = initial depth.

That is why the conclusion is the second statement of the answer choices: the pool must have been the same depth at the start of the interval as it was at the end of the interval.

In between the pool might have been deeper, more shallow, empty or change in any form, since the average rate of change does not tell the full history but only the net change.

"The pool must have been the same depth at the start of the interval as it was at the end of the interval" is the statement among the choices given in the question that must be true. The correct option among all the options that are given in the question is the second option. I hope the answer has helped you.

How long a line can you make using all the 3/8 inch strips

Answers

The length of the line calculated by using 3 / 8-inch strip will be ( 3/8 )x

What is an expression?

Expression in maths is defined as the collection of the numbers variables and functions by using signs like addition, subtraction, multiplication and division.

The total amount of line that the line will have depends on the number of strips, and the result is equal to the multiplication of the number of strips, x, and the length of the strips by 3/8 inch

Total length = ( 3/8 )x

where x is the number of strips, and the total length is in inches

Therefore the length of the line calculated by using 3 / 8-inch strip will be ( 3/8 )x.

To know more about expression follow

brainly.com/question/723406

#SPJ2

the total amount of lenght that the line will have depends on the amount of strips, and the result is equal to the multiplication of the amount of strips, x, and the length of the strips 3/8 inch

total_length = (3/8)x

where x is the amount of strips, and the total length is in inches

The product of (4z2 + 7z – 8) and (–z + 3) is –4z3 + xz2 + yz – 24. What is the value of x? What is the value of y?

Answers

Answer:

Hence, the value of x is 5 and y=29

Step-by-step explanation:

We are asked to find the product of 4z^2+7z-8 and (-z+3) and equate it to the equation:

-4z^3 + xz^2 + yz-24 and find the values of x and y in the second equation.

The product of  4z^2+7z-8 and (-z+3) is:

(4z^2+7z-8)*(-z+3)= (4z^2+7z-8)*(-z)+3* (4z^2+7z-8)\n=-4z^3-7z^2+8z+12z^2+21z-24=-4z^3+5z^2+29z-24

  Hence on comparing with -4z^3 + xz^2 + yz-24  we have:

-4z^3 + xz^2 + yz-24=-4z^3+5z^2+29z-24

so we get that x=5, y=29


x = 5 
y = 29

When you multiply the trinomial and the binomial, you get
-4z^3 + 5z^2 + 29z - 24 . The coefficient of the z^2 term is 5 and the coefficient of the z term is 29.